Interfacial reaction between SAC305 and SAC405 lead-free solders and electroless nickel/immersion silver (ENImAg) surface finish - Mohamed Anuar, Rabiatul Adawiyah (2017)
The different surface finish and solder size on printed circuit board strongly affect the formation of intermetallic compounds (IMCs) and solder joint reliability. Among of various surface finish in the electronic industry, electroless nickel/immersion gold is the most popular at the moment. However, because their black pad issues, electroless nickel/immersion silver (ENImAg) was developed as an alternative surface finish. Therefore, the effect on an interfacial reaction between lead-free solder and ENImAg surface finish using different solder ball size (Ø300μm, Ø500μm and Ø700μm) was investigated. All samples were subjected to an aging process with different aging times. The characterizations of IMC formation were examined by image analyzer, scanning electron microscopy and energy dispersive x-ray. The results showed that ENImAg finish was free from the black pad nickel. Subsequently, the solder ball size has a significant effect on the IMC formation and fracture surface of as-reflowed and aged solder joint. The IMC thickness of larger solder balls was found to be thicker (1.74 μm) than smaller solder balls (1.32 μm) during soldering. In contrast to aged solder joints, the smaller solder ball produced thicker (3.51 μm) IMC compared to bigger solder balls (2.47 μm). Furthermore, the fracture surface of smaller solder ball size showed ductile mode for both reflowed and aged solder joints. In addition, the solder joint on ENImAg surface finish displayed a thinner layer and smaller grain sizes compared to solder joint on bare copper.